2021
DOI: 10.1007/s00168-021-01066-x
|View full text |Cite
|
Sign up to set email alerts
|

Market fragmentation and the rise of sub-national regulation

Abstract: The evaluation of the Single European Market requires a better knowledge of the level of integration both between and within the EU countries. While some institutions are pushing for greater integration between EU countries, others may be introducing—purposely or collaterally—additional barriers to interaction. Several reports have reported the high levels of market fragmentation prevailing within Spain. This paper aims to determine whether regional borders influenced the patterns of intra- and interregional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Not for Redistribution due to the null and void declaration of key principals by the Spanish Constitutional Court in 2017, and as a result, regulatory differences across autonomous communities and municipalities have not improved materially. A recent study by Llano-Verduras et al (2021) found that fragmentation of the Spanish market has been increasing since the GFC, and that sub-national regulations have been significant contributors. An earlier study by the IMF (IMF, 2015) has stated the importance of product market competition on firm-level TFP by exploring cross-industry variations in ex-ante regulation stringency.…”
Section: Firm Marginal Cost Of Labor Across Age Groupsmentioning
confidence: 99%
“…Not for Redistribution due to the null and void declaration of key principals by the Spanish Constitutional Court in 2017, and as a result, regulatory differences across autonomous communities and municipalities have not improved materially. A recent study by Llano-Verduras et al (2021) found that fragmentation of the Spanish market has been increasing since the GFC, and that sub-national regulations have been significant contributors. An earlier study by the IMF (IMF, 2015) has stated the importance of product market competition on firm-level TFP by exploring cross-industry variations in ex-ante regulation stringency.…”
Section: Firm Marginal Cost Of Labor Across Age Groupsmentioning
confidence: 99%
“…Not for Redistribution due to the null and void declaration of key principals by the Spanish Constitutional Court in 2017, and as a result, regulatory differences across autonomous communities and municipalities have not improved materially. A recent study by Llano-Verduras et al (2021) found that fragmentation of the Spanish market has been increasing since the GFC, and that sub-national regulations have been significant contributors. An earlier study by the IMF (IMF, 2015) has stated the importance of product market competition on firm-level TFP by exploring cross-industry variations in ex-ante regulation stringency.…”
Section: Firm Marginal Cost Of Labor Across Age Groupsmentioning
confidence: 99%
“…Nevertheless, the application of the Market Unity Law remains slow due to the null and void declaration of key principals by the Spanish Constitutional Court in 2017, and as a result, regulatory differences across autonomous communities and municipalities have not improved materially. A recent study by Llano-Verduras et al (2021) found that fragmentation of the Spanish market has been increasing since the GFC, and that sub-national regulations have been significant contributors. An earlier study by the IMF (IMF, 2015) has stated the importance of product market competition on firm-level TFP by exploring cross-industry variations in ex-ante regulation stringency.…”
mentioning
confidence: 99%